Investigation of using bleaching earth and activated carbon mixturein sunfloweroilrefining - Gudret, Guliyev Nihad; Hikmet Jamal, Ibrahimov; Arif, Alekperov Jamil; Fariz Ali, Amirov; Meherrem, Ibrahimova Zenfira (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Adsorption is one commonly used technique for treatment of sunflower oil. In this study, activated carbon and bleaching earth as a bleaching agent mixed with certain proportions and1% of the mixture added to sunflower oil in the bleaching process. The combination of bleaching earth and activated carbon produced higher adsorption capacity than the single bleaching earth. This article focuses more particularly on heavy metals and polycyclic aromatic hydrocarbons (PAHs) removal. It was detected that, the mixture is an excellent adsorbent in the adsorption of PAHs and metals from sunflower oil with the highest adsorption capacity. The results showed that, the adsorption of metals and PAHs depend strongly on activated carbon and decreased with increasing activated carbonin mixture and the maximum adsorption was reached after using B5 (95 % bleaching earth and 5 % activated carbon combination).